UTILIZING POST PROCESSING KINEMATIC (PPK) UNMANNED AERIAL VEHICLE (UAV) TO ACCELERATE DETAILED LAND MAPPING - Regita Faridatunisa Wijayanti; Niswah Selmi Kaffa; Taufik Kusetiyohadi; Hesekiel Sijabat; Angga Pratama Putra; Septa Erik Prabawa; Yunus Susilo (Jurnal Geosaintek, 2023)
The accelerate of land registration is important to solve the land disputes. Start from 2022, BPN utilize UAV to make base maps quickly. One of photo map criteria is high horizontal accuracy of <0.5 meter by using Circular Error 90% (CE90). This research analyzes the effectiveness of PPK method on UAV survey to accelerate detailed land mapping in Indonesia. UAV fixed wing Vertical Takeoff and Landing (VTOL) model with Sony ILCE-6000 camera flown on 9.46 km2 areas, flying on 244 meters, and using 8 Ground Control Points (GCP) in Muktisari Village, Ciamis. First, UAV camera coordinates processed to obtain photo mosaic. Furthermore, geometric correction processed with GCP to obtain orthophoto for each mosaic photo. The UAV without PPK produced CE90: 0.02 meter (RMSE: 0.013 meter), whereas the UAV using PPK produced CE90: 0.008 meter (RMSE: 0.005 meter). According to the CE90 value on UAV showed resulting photo map included in 1:1000 scale aerial photo map in class 1. However, this research showed the UAV using PPK is 2.5 times more accurate. In conclusion, PPK can improve the performance of UAV to increase the photo map geometry accuracy. Hence, UAV using PPK are recommended to accelerate detailed land mapping in Indonesia.